Gastrointestinal disease is an important influencing factor of osteoporosis fracture:a retrospective study in chinese postmenopausal women - PengChao Xu; JiRong Ge; Hong Jiang; YuJuan Lin; YunJin Ye; XiaoBin Huang; YanYan He; LiPeng Xue (BMC Musculoskeletal Disorders, 2023)
Abstract Backgroud The influencing factors of osteoporosis are complex, the incidence of osteoporosis is higher in middle-aged and elderly women, and osteoporotic fractures (OF) can seriously affect quality of life. Currently, the correlation analysis between gastrointestinal diseases and OF focuses more on diseases such as gastric cancer and inflammatory bowel disease (IBD). This study analyzed the risk factors for osteoporosis and osteoporotic fractures in 1567 postmenopausal women in Fuzhou, China. The purpose is to explore the potential influence of gastrointestinal diseases on the occurrence of OF. Methods According to inclusion and exclusion criteria, a total of 1567 subjects were included in the analysis of OP risk factors, including 647 in the OP group and 920 in the NOP group. A total of 616 subjects were included in the analysis of correlation between OF and gastrointestinal diseases, including 132 in OF group and 484 in NF group. Statistical analysis shows that age (OR = 1.062, 95% CI = 1.045–1.080), height (OR = 0.089, 95% CI = 0.009–0.857), weight (OR = 0.981,95% CI = 0.967–0.995) and nature of work (P = 0.010) are the main risk factors for osteoporosis in postmenopausal women in southeast China, and gastrointestinal diseases (OR = 1.583, 95% CI = 1.070–2.343) and height (OR = 0.003, 95% CI  = 0.000-0.104) are the main risk factors of OF. Conclusions The main factors affecting the occurrence of OP in postmenopausal women in southeast China are individual characteristic. Gastrointestinal diseases that do not directly affect BMD increase the risk of OF in osteoporotic patients.